Optimalisasi Konsep Octane Cycle sebagai Strategi Pengolahan Sampah Terpadu Menuju Desa Zero Waste di Argosari, Malang: Optimalisasi Konsep Octane Cycle sebagai Strategi Pengolahan Sampah Terpadu Menuju Desa Zero Waste di Argosari, Malang - Musyaroh; Anisah Nurul Izzah; Rizqa Ruviana; Luluk Edahwati; Dewi Maya Maharani (Dharmakayana, 2025)
Argosari Village faces a critical waste management challenge due to the accumulation of biogas slurry (300–500 kg/day), household waste (687 kg/day), and agricultural waste (1,919.7 kg/day). Limited public awareness and waste processing capacity have led to uncontrolled environmental pollution. This community service program introduces the Octane Cycle Concept, a novel and integrative waste utilization model that transforms both organic and inorganic rural waste into valuable products such as compost, fertilizers, fish feed, mushroom media, and handicrafts. The Octane Cycle emphasizes a closed-loop, multi-output processing approach that links food, energy, and local economy in a zero-waste framework. The program was carried out in five phases: preparation, equipment provision, community training, monitoring and evaluation, and reporting. Results show that waste volume in Argosari Village was reduced by 51% within three months. In addition to improving environmental cleanliness, the program fostered entrepreneurship and increased household savings through the production of bio-based products. This model demonstrates the scientific and practical potential of applying circular economy principles at the village level.